Optimization of the configuration of prefabricated elements for the rapid assembly of low-rise buildings - RASHKIVSKYI, Volodymyr; CHERNENKO, Kostiantyn (Ways to Improve Construction Efficiency, 2025)
The article investigates the complex problem of optimizing the configuration and logistics of prefabricated elements used for the rapid assembly of low-rise buildings (in particular, using modular and prefab construction technologies). The relevance of the topic is determined by the need to accelerate the pace of construction of residential and infrastructure buildings in the context of Ukraine’s post-war reconstruction, as well as global trends in the transition to industrial construction methods. The essence and differences of the concepts of "modular construction" and "prefab structures" are analyzed, and their key advantages over traditional construction methods are highlighted. Special attention is paid to the logistics aspect, as transportation costs can account for up to 35% of the total estimated cost of construction. The paper presents calculations of the weighted average transport distance and a comparative analysis of pendulum, circular, and one-way transport schemes. It is proved that the choice of an optimal supply scheme from the manufacturing plant (for example, a plant of reinforced concrete or metal structures) directly to the construction site can reduce transportation costs by more than 40%. The article presents a comparative analysis of the Life Cycle Cost (LCC) of traditional and innovative (energy-efficient) modular buildings, confirming the long-term economic benefits of the optimized configuration of high-tech prefabricated elements. Recommendations are developed for organizing rhythmic construction flows (with a step of 1-3 days) to ensure continuous and efficient assembly. The study results are of high practical significance for contractors, developers, and logistics operators seeking to minimize costs and shorten construction times while maintaining the highest levels of quality and safety.